Morphologic study of nutrient foramina in dried tibia and its clinical implications - T, Jayaprakash (International Journal of Medical Research and Review, 2016)
Introduction: Diaphyseal fractures of tibia cases are common in orthopaedics and traumatology department. While planning a bone graft for a patient with trauma or tumour resection, the vascularity of the left over bone in the donor site is important as it influences the choice of graft to be used. Methodology: The study was conducted on 50 adult dried tibiae. Diaphyseal nutrient foramina were identified by their elevated margins and by the presence of a distinct groove proximal to them. Foramen index was calculated. Results: All the foramina were present on the posterior surface. Most of the (80%) nutrient foramina were present lateral to vertical line (17 on the right and 23 on the left side). Eight nutrient foramina were present on the vertical line. Only two nutrient foramina were present medial to vertical line. The mean foramen index between right and left tibiae was 32.99 ± 1.87 and 34.36 ± 6.24 respectively. Majority (82%) of nutrient foramina were found on upper zone, 18% were observed on middle zone and none were found on the lower zone. Conclusion: Scarcity of nutrient foramina in the middle and lower 1/3rd of the shaft indicates poor blood supply to this region of bone which may account for delayed union or non union of the fractures at the lower part of the bone.